The Effects of Ti Additions and Deposition Parameters on the Structural and Mechanical Properties of Stainless Steel-Nitride Thin Films - Faisal I. Alresheedi (Coatings, 2019)
This study examines the structure and properties of stainless steel coatings deposited to incorporate large concentrations of nitrogen along with varying amounts of titanium. Deposition was carried out using magnetron co-sputtering of stainless steel and titanium from separate targets in a mixed Ar/N2 gas atmosphere. Composition analysis by X-ray photoelectron spectroscopy showed that while films with up to 4 at.% Ti exhibited little change in nitrogen content (compared to films deposited without Ti) and remained sub-stoichiometric with respect to N content. Films with 7−8 at.% Ti had a higher N level and further increasing the Ti level to 11−12 at.% resulted in stoichiometric N levels. X-ray diffraction showed that the films all had a nominally FCC structure with no additional phases. However, the peak locations for the (111) and (200) reflections indicated a distorted lattice characteristic of the S-phase, with calculated c/a values ranging from 1.007 to 1.033. The Ti additions, along with the corresponding increase in N content, helped reduce the extent of lattice distortion. The film microstructure of the higher (11−12 at.%) Ti films also showed higher density, lower surface roughness, and a finer grain structure. As a result, these films had a higher hardness compared to the sub-stoichiometric films, with hardness levels in the range of 18−23 GPa, typical of transition metal nitrides coatings.